THU0224 Randomized Double-Blind Comparative Effectiveness in RA Patients with Active Disease Despite Methotrexate (MTX): A Comparison of Conventional Disease-Modifying Anti-Rheumatic Drugs with a Biological. (23rd January 2014) - O'Dell, J. R.; Mikuls, T. R.; Taylor, T.; Ahluwalia, V.; Brophy, M.; Warren, S.; Lew, R.; Phibbs, C.; Anis, A. H.; Cannella, A. C.; Kunkel, G. A.; Keystone, E.
Abstract : Background: Double-blind placebo controlled trials have demonstrated the efficacy of 16 different therapies in RA patients with active disease despite MTX. However, there have been no blinded trials comparing conventional combination therapy to biologicals in this population. This gap in knowledge is important since biologicals are substantially more expensive than conventional therapy and have different toxicities. We compared two treatment strategies, adding conventional oral DMARDs or adding a biological, etanercept, in patients with active disease despite MTX followed by switch to the other treatment when clinically indicated. Methods: This investigator-initiated multinational double-blind non-inferiority trial randomized 353 patients with active RA despite MTX to treatment with triple DMARD therapy (MTX, sulfasalazine and hydroxychloroquine) or etanercept + MTX. Treatment continued for 48 wks, with blinded treatment switch at 24 wks for patients in either group if their disease activity had failed to improve by a clinically significant amount (ΔDAS28 of <1.2). The primary end point was DAS28 improvement at wk 48 based on the initial randomization. Radiographic progression, physical functioning and pain were secondary endpoints. Patients were enrolled from 16 VA centers, 12 other US sites and 8 sites in Canada. Results: Study population baseline characteristics: mean age 57 yrs, 54% males, DAS28 = 5.8, disease duration 5.2 yrs and mean initial MTX dose 19.6 mg/wk. There were no significant differences between groups at baseline. Both groups improved significantly over 24 wks (p=0.001). The proportion of patients requiring a switch at 24 wks was nearly identical (27.0% for triple and 26.7% for etanercept). In patients who switched, both groups improved significantly (p <0.0001) and the response was not different between therapies (p=0.08). At 48 wks the change in DAS28 was virtually the same based on initial randomization (-2.1 [triple] and- 2.3 [etanercept]). Importantly, for patients in either group who had responded at wk 24 (73% of the patients) the response was maintained at 48 wks. Radiographic progression was minimal and not different between groups (+ 0.54 for triple vs + 0.29 for etanercept, [p=0.43]). Secondary patient-reported outcomes HAQII, pain, EQ-5D were also not different. Comparing the direct medication costs of the two strategies, the difference of the drug costs alone between triple DMARD and etanercept is $10, 200 per patient year. Conclusions: The strategy of continuing MTX with the addition of sulfasalazine and hydroxychloroquine is comparable to adding etanercept in RA patients with active disease despite MTX and results in similar benefits in disease measures, function and radiographic progression. At the health system level, the cost-saving potential and the cost-effectiveness of the strategy of starting with conventional DMARD combinations and then switching to biologicals in those who do not respond may be substantial. Acknowledgements: Funding Sources: Cooperative Studies Program of the Department of Veterans Affairs Office of Research and Development, CIHR and NIAMS by interagency agreements. Placebo etanercept donated by Amgen Disclosure of Interest: J. O'Dell: None Declared, T. Mikuls Grant/research support from: Genentech, T. Taylor: None Declared, V. Ahluwalia Grant/research support from: Abbott, Janssen, Roche, UCB, Consultant for: Abbott, Amgen/Wyeth, BMS, Janssen, Roche, Speakers bureau: Abbott, Janssen, Roche, M. Brophy: None Declared, S. Warren: None Declared, R. Lew: None Declared, C. Phibbs: None Declared, A. Anis: None Declared, A. Cannella: None Declared, G. Kunkel: None Declared, E. Keystone Grant/research support from: Abbott Laboratories; Amgen, Inc.; AstraZeneca Pharmaceuticals LP; Bristol-Myers Squibb; Centocor, Inc.; F. Hoffmann-LaRoche Inc.; Genzyme, Merck, Novartis Pharmaceuticals, Pfizer Pharmaceuticals, UCB, Consultant for: Abbott Laboratories; AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company; Centocor, Inc.; F. Hoffmann-LaRoche Inc.; Genentech Inc.; Merck, Nycomed, Pfizer Pharmaceuticals, UCB, Speakers bureau: Abbott Laboratories; Bristol-Myers Squibb Co.; F. Hoffmann-LaRoche Inc.; Merck; Pfizer Pharmaceuticals; UCB; Amgen; Abbott, Janssen Inc.